KEHIDUPAN ANAK JALANAN DI INDONESIA: FAKTOR PENYEBAB, TATANAN HIDUP DAN KERENTANAN BERPERILAKU MENYIMPANG - Astri, Herlina (Jurnal Aspirasi, 2014)
Becoming street children is not a desirable option to everyone, especially for security issues. Street children often seen as a problem, and there are no regulations yet to overcome this phenomenon. This paper uses the study of literature, to explore the causes, way of life, and the vulnerabilities faced by street childrencaused them tend to behave deviantly.Results of the study indicates that the presence of street children mostly caused by poverty, personality disorder, and external factors of the child. They have their own way of life and are oftenly regarded as the dregs of society. Unfavorable streetlife conditions and the lack of supervision from the family makes street children are particularly vulnerable to various forms of violence.To solve the problems of street children, a comprehensive change is needed so that they will not live and workin the street again.